Business Planning : Shadow Burger Enterprise / Mohd Ali Fahmi Sahar ...[et al.] - Sahar, Mohd Ali Fahmi; Mohd Yusof, Azizan; Zainal Abiden, Muhamad Faiz Naim; Md Idris, Md Rafy (2009)
Shadow Burger Enterprise is a 100% company owned by bumiputra. The name of the company is selected once the approvals from all partners have been received. We are focusing on producing ‘Fast Food’ which is a food product which is categorized under traditional snack. Our office and factory is located at Lot 63, Jln Tanjung, 18500 Machang, Kelantan Darul Naim. This company is managed by competent and skilled graduates. The industry that we choose here is a very profitable industry with the estimation by more than 200 entrepreneurs producing ‘fast food’ throughout the country. Fast Food is identified as one of the food products to be promoted under easy get a food programme. We are interested in this field because although there are so many entrepreneurs involve in producing ‘Fast Food’ and attempts to introduce the product globally, the inconsistency of product quality and specification have held back its penetration. This is because of inconsistent production method which contributes to low quality product. We are determined to resolve this difficulty and be a sole provider in producing ‘fast food’